Kompetence vojaškega voditeljstva na direktni ravni za izzive prihodnosti - Kovačić, Zoran (Revija za univerzalno odličnost, 2025)
Research Question (RQ): Which additional competencies of military leadership at the direct level are essential for successful command and leadership in military organizations in future? Purpose: The purpose of the research is to identify additional competencies of military leadership at the direct level are essential for successful command and leadership in military organizations in future. Method: For data analysis, we used a descriptive research design for sources dealing with military leadership, primarily sources from NATO member states. Through description, comparison, and induction methods, we triangulated the additional competencies of military leadership that are expected to contribute to the success of military organizations in future tactical-level tasks. Results: Key additional competencies of future military leadership identified as critical for the success of military organizations are: mental resilience, cognitive agility, and technological literacy. Organization: Results of military leadership at the direct level within a military organization will depend on its ability to adapt to new challenges and needs. By investing in education, developing methodologies for assessing potential, and utilizing modern technologies, a military organization can create an effective and flexible leadership structure ready to face 21st-century challenges. Society: Successful contribution to national and international security levels. Originality: The topic of developing military leaders´ competencies at the direct level for future challenges has not yet been satisfactorily addressed in the field of military leadership. Limitations / further research: Due to time limitation research does not include surveys and interviews with military leaders at various levels and within different organizational units in the Slovenian Armed Forces regarding challenges for direct-level military leadership. The written article is a theoretical framework for future research in PhD dissertation.
Keywords: direct level; direktna raven; kognitivna agilnost; kompetence; leadership competencies; mentalna odpornost; military leadership; military organizations; Oborožene sile; Poveljevanje; Sposobnost; tehnološka pismenost; Vodenje; vojaške organizacije; vojaško voditeljstvo